2019
DOI: 10.1007/s12182-019-00404-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential of surface-modified silica nanoparticles using internal olefin sulfonate for enhanced oil recovery

Abstract: Recently, nanoparticles have proven to enhance oil recovery on the core-flood scale in challenging high-pressure high-temperature reservoirs. Nanomaterials generally appear to improve oil production through wettability alteration and reduction in interfacial tension between oil and water phases. Besides, they are environmentally friendly and cost-effective enhanced oil recovery techniques. Studying the rheological properties of nanoparticles is critical for field applications. The instability of nanoparticle d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Sharma et al [ 16 ] observed that IFT was reduced in a brine/oil system by almost half of the initial, after adding 1 wt.% of SiNPs. Ahmed et al [ 17 ] reported that IFT in an oil/brine system decreased by three times its original value after surface-treated SiNPs were added to the brine. They observed that IFT reduction was more significant when the concentration of NPs was increased.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al [ 16 ] observed that IFT was reduced in a brine/oil system by almost half of the initial, after adding 1 wt.% of SiNPs. Ahmed et al [ 17 ] reported that IFT in an oil/brine system decreased by three times its original value after surface-treated SiNPs were added to the brine. They observed that IFT reduction was more significant when the concentration of NPs was increased.…”
Section: Introductionmentioning
confidence: 99%
“…The critical NP concentration obtained in case of surfactant‐polymer‐nanoparticle (SPN) fluids is lower (0.025 wt.%) as compared to that obtained for surfactant fluids (0.030 wt.%). Beyond this limit, IFT was observed to increase gradually owing to improved steric effect in the presence of higher concentration species 59,60 . This indicated desorption of interacting molecules/particles from the interface to the bulk solution phase and consequent transition of mixed micelles to super micelles or vesicles 59,60 .…”
Section: Resultsmentioning
confidence: 98%
“…Beyond this limit, IFT was observed to increase gradually owing to improved steric effect in the presence of higher concentration species 59,60 . This indicated desorption of interacting molecules/particles from the interface to the bulk solution phase and consequent transition of mixed micelles to super micelles or vesicles 59,60 . SPN fluids are able to recover oil with IFT values in the desired optimal range and sweep crude oil with greater efficacy as compared to surfactant‐nanoparticle and surfactant formulations.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle is an influential parameter for determining wettability alteration, relative permeability curves, and capillary pressure. These parameters have significantly affected the oil recovery performances, as they has been affected by the water–wet or oil–wet property between rock surface and fluid [ 76 , 77 ]. The contact angles were measured for polymer and water treatment on the surface area in the presence of various nanoparticles concentrations (SiO 2 nanoparticle).…”
Section: Resultsmentioning
confidence: 99%